(untitled) (Italian Journal of Public Health, 2010)
Background: Injury as a cause of significant morbidity and mortality has remained fairly stable in countries with developed economies. Although injury prevention often is conceptualised as a biomedical construct, such a reductionist perspective overlooks the importance of the psychological, environmental, and sociocultural conditions as contributing factors to injury and its consequences. This paper describes the potential of the ecological model for understanding the antecedent causes of unintentional injuries and guiding injury prevention approaches. We review the origins and conceptualise the elements of the ecological model and conclude with some examples of applications of ecological approaches to the prevention of unintentional injury and promotion of community safety. Methods: A review of the English-language literature on the conceptualization of ecological models in public health and injury prevention, including the application of the ecological model in the prevention of falls and road traffic injuries and in the community safety promotion movement. Results: Three dimensions are important in social-ecological systems that comprise key determinants of injuries: 1) the individual and his or her behaviour, 2) the physical environment, and 3) the social environment. Social and environmental determinants have profound impact on population health and in the causation of injuries. Conclusions: Social and environmental determinants of injury should be studied with the same energy, urgency, and intellectual rigor as physical determinants. Application of the ecological model in injury prevention shows the most promise in falls injury prevention, road traffic injury prevention, and community safety promotion.